IBM DS8900F performance best practices and monitoring - Kimmel, Peter; Brunson, Sherri; Martinez, Lisa; Moreira, Luiz Fernando; Palacio, Ewerson; Pekosh, Rick; Rizvi, Ali; Smith, Paul (IBM Redbooks, 2021)
This IBM℗ʼ Redbooks℗ʼ publication is intended for individuals who want to maximize the performance of their DS8900 storage systems and investigate the planning and monitoring tools that are available.
Includes bibliographical references
Keywords: Storage area networks (Computer networks); IBM computers; Operating systems (Computers); Computer architecture; Client/server computing; Réseaux de stockage (Informatique); IBM (Ordinateurs); Systèmes d'exploitation (Ordinateurs); Ordinateurs; Architecture; Architecture client-serveur (Informatique); operating systems